THE STARTUP RETENTION DILEMMA: EXAMINING THE INFLUENCE OF COMPENSATION AND ORGANIZATIONAL CULTURE ON TURNOVER INTENTION THROUGH THE MEDIATION OF JOB SATISFACTION - Rohman, Abdul; Parimita, Widya (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
Turnover intention refers to an employee"™s inclination to leave the company or organization. This study aims to analyze and examine the significant influence of compensation and organizational culture on the turnover intention among startup employees in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, and Bekasi) area, with job satisfaction serving as a mediating variable. This quantitative study collected the data through a questionnaire distributed to 242 respondents, which was then analyzed using SmartPLS 3.0. The results show that the compensation has a positive and non-significant influence on the job satisfaction. However, it has a negative and statistically significant influence on the turnover intention. Additionally, when mediated by the job satisfaction, it has a positive and non-significant influence on the turnover intention. On the other hand, the organizational culture has a positive and statistically significant influence on the job satisfaction, while negatively affecting the turnover intention. Furthermore, it also has a positive and non-significant influence on the turnover intention when mediated by the job satisfaction. Lastly, the job satisfaction has a positive and non-significant influence on the turnover intention.JEL: M13, M14.